Meta-analysis of substitution value of maize with cassava (Manihot esculenta Cratnz) on growth performance of broiler chickens - Ogbuewu, Ifeanyichukwu Princewill; Mbajiorgu, Christian Anayo (Frontiers in Veterinary Science, 2022)
There are variable results on the effect of cassava and cassava products on performance characteristics of broiler chickens. As a result, this meta-analysis aimed to determine the effect of cassava and cassava products on feed intake, feed conversion ratio (FCR) or average daily gain (ADG) of broiler chickens. A methodical search using Google Scholar, Scopus, Web of Science and PubMed databases was performed and 365 articles were identified. Twenty-three of 365 studies met the inclusion criteria and were used for the analysis. Response variables were pooled using random-effects model and results expressed as standardized mean difference (SMD) at 95% confidence intervals (CIs) for each study. Subgroup and meta-regression analyses were used to evaluate the effect of covariates (broiler strain, inclusion level of cassava, number of broilers per replicate, cassava processing methods and cassava form) on response variables. Results indicated that cassava had a small effect on feed intake (SMD = -0.07, 95% CI - 0.26, 0.12) and FCR (SMD = 0.14; 95% CI 0.82, 1.746), but a large effect on ADG (SMD = -1.67; 95% CI - 1.99, - 1.35) compared to controls. Subgroup analysis results show that wet fermented cassava peel meal (WFCPM) had a moderate impact on feed intake (SMD = 0.62, 95% CI 0.47, 0.77) and ADG (SMD = 0.66, 95% CI 0.37, 0.95) in comparison with controls. Our results also found that broiler chickens fed cassava at 4-10% were similar in performance to controls. There is evidence of between-study variance and studied covariates explained most of the sources of heterogeneity. In conclusion, the present study suggested that inclusion of WFCPM at 4 to 10% improved growth performance characteristics of broiler chickens.